2016
DOI: 10.1097/01.naj.0000505585.47708.ac
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biological Interventions for Ulcerative Colitis on Health-Related Quality of Life

Abstract: Editor's note: This is a summary of a nursing care-related systematic review from the Cochrane Library.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[ 3 ] Due to the disease's long duration and wide range of pathological changes, recurrences can sometimes occur even during remission, seriously affecting quality of life. [ 4 , 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Due to the disease's long duration and wide range of pathological changes, recurrences can sometimes occur even during remission, seriously affecting quality of life. [ 4 , 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…Its main symptoms include abdominal pain, diarrhea and mucus, pus and blood. Some UC patients have extra-intestinal manifestations and complications, which affect their daily lives, and even their health (Whitehead 2016 ; Sykora et al 2018 ). An epidemiological survey reported higher prevalence of UC among the people of 20–40 years, and higher prevalence in males than females (Lewin et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews and meta-analyses concluded that biologics have the potential to improve health-related QoL in patients with ulcerative colitis [45][46][47] . Indeed, there is now good evidence demonstrating that treatment with biological agents will lead to meaningful benefits on QoL.…”
Section: Biological Therapies and Quality Of Lifementioning
confidence: 99%